The predictive effect of platelet recovery on the prognosis of severe fever with thrombocytopenia syndrome - Tian, Bing; Gao, Yuan; Sheng, Qiyue; Mao, Xuelan; Wang, Jinyong; Zhang, Shujun; Peng, Jingxia; Li, Lijia; Hou, Yumeng; Chen, Jingyi; Wang, Zhiqian; Di, Yu; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSevere fever with thrombocytopenia syndrome (SFTS), an emerging infectious disease, has a high case fatality rate (CFR) in severe patients. Thrombocytopenia is one of the features of SFTS, and a platelet count lower than 50×109/L is a risk factor for mortality in patients with SFTS. However, there have been no studies on the value of platelet recovery in the prognosis of SFTS patients.MethodsFrom January 2009 to December 2020, laboratory-confirmed severe SFTS patients with platelet counts lower than 50×109/L were enrolled and divided into a survival group and a death group based on 90-day prognosis. Descriptive analysis of baseline data compared characteristics between the survival and death groups. Multivariate Cox proportional hazards regression models identified independent mortality risk factors for SFTS patients. A nomogram-presented prediction model was constructed via multivariate Cox regression. The performance of nomogram was measured by the receiver operating characteristic (ROC) curve, calibration diagram, and decision curve analysis (DCA).Results144 SFTS patients with platelet counts< 50×109/L during the disease were included. After three months of follow-up, 109 patients survived and 35 patients died. The cut-off values for predicting fatal outcomes were 40×109/L for platelet levels on day three (PLT Day3) and 50×109/L for platelet levels on day five (PLT Day5), respectively. Statistical analysis showed a significant difference (p<0.001) in platelet recovery to these levels within 3 or 5 days. Kaplan-Meier analysis showed that patients with unrecovered PLT on day 5 had a higher cumulative incidence of mortality than those with recovered PLT on day 5. Multivariate Cox regression found age ≥65, failure of platelet count to reach 50×109/L in 5 days, prolonged APTT, and elevated LDH as independent mortality risk factors (p<0.05). Subgroup analysis showed a significant association between whether the platelet count recovers to 50×109/L within 5 days (PLT-Day5) and mortality in all subgroups.ConclusionsWhether the platelet count recovers to 50×109/L within 5 days (PLT-Day5), aspartate aminotransferase (APTT), lactate dehydrogenase (LDH) and age are independent predictors of mortality in severe SFTS patients with platelet counts below 50×109/L during the course of the disease. Patients whose platelet count recovers from the lowest value to 50×109/L within five days have a better prognosis.